Transdermal Semaglutide Administration in Mice: Reduces Body Weight by Suppressing Appetite and Enhancing Metabolic Rate - Wenjing Li; Ruilin Cai; Binxin Yin; Yingying Zhou; Xinyuan Dong; Wenting Li; Jing Wen (Biology)
Background: Semaglutide is a glucagon-like peptide-1 (GLP-1) receptor agonist that shows significant efficacy in treating obesity. However, its associated side effects, including poor patient compliance and gastrointestinal inflammation, are concerning and may be largely attributed to its administration methods (e.g., injection vs. oral) and the pronounced fluctuations in systemic drug concentrations. To address these challenges, we investigated an innovative drug delivery system (Transdermal Drug Delivery System, TDDS) designed to maintain therapeutic efficacy while improving patient adherence. Results: Both transdermal and injection treatments of semaglutide decreased body weight, carcass weight, blood glucose, and triglyceride levels in male mice compared with the vehicle-treated control group. In addition, transdermal semaglutide in mice reduced the expression of feeding neuropeptides and the mass of the digestive tract, but increased brown adipose tissue (BAT) mass, metabolic rate, and physical activity, compared with the semaglutide injection group. Additionally, transdermal semaglutide had anxiolytic effects on behavior and did not alter tissue pathology in mice. Conclusion: Compared with the injection paradigm, transdermal semaglutide treatment achieved superior weight loss results in two possible ways: It may reduce energy intake by decreasing the expression of feeding neuropeptides and reducing the weight of the digestive tract. It may also facilitate energy expenditure by enhancing physical activity and increasing BAT mass to boost the metabolic rate. Transdermal semaglutide treatment also has an anxiolytic effect on behavior. Together, our data suggest that TDDS treatment of GLP-1RA may have superior clinical safety and sustainability, providing a novel, efficient, and low-risk obesity treatment.